2020
DOI: 10.3390/su12083090
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Information and Pre-Employment Background Checks: The Mediating Role of Sustainable Organizational Reputation

Abstract: This study was aimed at identifying the role of social networking information (SNI) on pre-employment background checks (PBCs) of job applicants involving a single mediating variable, sustainable organizational reputation (SOR). In addition to that, we conducted a multi-group analysis to examine whether the direct and mediating effects were stronger in terms of gender difference. For investigation, a structured questionnaire was utilized to collect data from 1138 respondents working as hiring professionals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…As it was observed, PAI had a noteworthy positive influence (β 5 0.117; p < 0.05) on PBC accepting of the first hypothesis. This result is consistent with the previous theoretical arguments since numerous authors reported that the hiring managers seek more information available from SNSs (Hosain et al, 2020;Hosain and Liu, 2020a;Pramod and Bharathi, 2016;Ebnet, 2012). On the other hand, PACI had positive influence (β 5 0.038) on PBC (consistent with previous literature) although the influence was not significant (p > 0.05) which is also supported by Drake et al (2016) where the authors revealed that the hiring managers, in many cases did not pay much attention to information accuracy.…”
Section: Discussion Of Results Linking Previous Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…As it was observed, PAI had a noteworthy positive influence (β 5 0.117; p < 0.05) on PBC accepting of the first hypothesis. This result is consistent with the previous theoretical arguments since numerous authors reported that the hiring managers seek more information available from SNSs (Hosain et al, 2020;Hosain and Liu, 2020a;Pramod and Bharathi, 2016;Ebnet, 2012). On the other hand, PACI had positive influence (β 5 0.038) on PBC (consistent with previous literature) although the influence was not significant (p > 0.05) which is also supported by Drake et al (2016) where the authors revealed that the hiring managers, in many cases did not pay much attention to information accuracy.…”
Section: Discussion Of Results Linking Previous Findingssupporting
confidence: 92%
“…Therefore, even a candidate may have got a social networking profile; it is not certain for an employer to avail all the required information to screen a candidate for background checking process (Hosain et al, 2020).…”
Section: Perceived Availability Of Information (Pai)mentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational reputation can result from applying ideas about positively affecting the customers toward the organization and its influence on potential and present employees [28]. Such reputation can be maintained if the organizational objectives and policies can be aligned with the customers' preferences, even if they face risks and uncertainty [29]. The purpose of such reputation management is to collect information and opinions, understand, forecast, and deal with them systematically to manage a solid and sustainable corporate profile.…”
Section: Perceived Organizational Support (Pos) Sustainable Organizational Performance (Sop) and Sustainable Organizational Reputation (Smentioning
confidence: 99%
“…SOR4: Sustainable organizational reputation is the basis of sustainable organizational performance. Ambrose and Schminke [12]; Hosain et al [29]; and Dögl and Holtbrügge [33] SOR3: An organization with a sustainable reputation can gain the trust of internal and external stakeholders. SOR2: Employees want to stay with an organization having a sustainable reputation.…”
Section: Sustainable Organizational Reputation (Sor)mentioning
confidence: 99%